Peasant Rights and the Struggle for Climate Justice in Indonesian Degraded Peatland - Safitri, Myrna Asnawati; Sihite, Dermawati; Yusuf, Muhammad (University of Jember, 2025)
The United Nations Declaration on the Rights of Peasants and Other Peoples Working in Rural Areas (UNDROP) recognizes and protects the dignity of peasants for their contributions to food production and climate change mitigation and adaptation. For Indonesia, signing UNDROP complements its international commitments to human rights and environmental protection, particularly climate change. Indonesia has ratified the Paris Agreement, which includes climate change mitigation in peat ecosystems as one of its agendas. At the regional level, Indonesia supports the ASEAN Human Rights Declaration and the ASEAN Transboundary Haze Agreement. The Indonesian government has established a zero-tolerance policy towards peatland burning. This policy has resulted in legal vulnerability for peasants who have a tradition of burning peatlands for agriculture. This article examines the influence of laws and policies to control forest and land fires as a form of climate change mitigation in protecting peasants' rights to food and a better environment. In particular, it discusses community-based and participatory approaches to peatland ecosystem restoration implementation in Indonesia and how they relate to the provisions of UNDROP. The research underpinning this article used a participatory legal research method involving the authors in policy making. The authors collected data and analysed laws and policies concerning peatland restoration and peasants' protection. The participatory observation was carried out on agricultural innovation practices and the legal empowerment of the peasants. This article concludes that although UNDROP is not used as a reference in forming peatland restoration policies, some activities have demonstrated the fulfilment of several UNDROP provisions Keywords: Climate change, peatland, peasants, right to food, UNDROP